ISOLATION AND CHARACTERIZATION ISOLATES OF NOSOCOMIAL INFECTIONS - Korotetskiy I. S.; Jumagaziyeva A. B.; Reva O. N.; Kuznetsova T. V.; Shvidko S.V; Iskakbayeva Z. А.; Myrzabayeva A. Н.; Ilin A. I (Scientific Journal of Pedagogy and Economics, 2019)
The study aimed to identify clinical isolates of nosocomial infections to characterize and create a Bank of strains to study the phenomenon of reversion of antibiotic sensitivity in different types of pathogenic bacteria. Methods: Clinical isolates from patients suffering from nosocomial infections were plated on respective media to obtain pure cultures, which then were identified and characterized by morpho-cultural, tinctorial, physiological and biochemical traits carried out using standard test systems. The antibiotic sensitivity profile of clinical isolates was studied by the disco-diffusion method. Isolation of DNA from bacteria was carried out using the PureLink Genomic DNA Kit. DNA library for sequencing was obtained by the enzymatic approach using the Ion Xpress Plus Fragment Library Kit (Life Technologies, USA). Barcoding of isolates was carried out using the Xpress Barcode Adapters Kit (Life Technologies, USA). Sequencing of the resulting library was carried out on 318 chips using the Ion PGM Hi-Q View Sequencing Kit. Quality of the reads and trimming of DNA fragments were carried out using the computer programs fastqc and Cassava fastq filter. Genome fragments were assembled using Velvet 1.2.10. Large genome fragments were used to search for the closest reference genomes in the NCBI database. The complete genomes of the isolates were used as reference sequences for an alignment of the generated DNA reads using the program bowtie2. The completeness of the final assemblies was evaluated by the program BUSCO. Genome annotation was carried out using the NCBI annotation pipeline. The results of the quantitative studies were processed using one-way ANOVA single-factor variance analysis followed by a statistical analysis using the software package GraphPad Prism 6. In total, 12 clinical isolates were obtained. Complete genome sequence of four isolates was determined - Enterococcus faecalis PHRX1, Pseudomonas aeruginosa WND1-2019, P. aeruginosa WND2-2019, and P. aeruginosa WND3-2019. Annotated genomes were deposited at the NCBI database.